Frequency-Dependent Effects of Cerebellar Repetitive Transcranial Magnetic Stimulation on Visuomotor Accuracy - Lien, Yun R.; Lin, Yi-Cheng; Lin, Shang-Hua N.; Lin, Ching-Po; Chang, Li-Hung (Frontiers in Neuroscience, 2022)
The cerebellum plays a critical role in acquiring visuomotor skills. Visuomotor task mastery requires improving both visuomotor accuracy and stability; however, the cerebellum’s contribution to these processes remains unclear. We hypothesized that repetitive transcranial magnetic stimulation (rTMS) of the cerebellum exerts frequency-dependent modulatory effects on both accuracy and stability in subjects performing a visuomotor coordination task (i.e., pursuit rotor task). We recruited forty-three subjects and randomly assigned them to high-frequency (HF), low-frequency (LF), and sham rTMS groups. We calculated changes in performance of the pursuit rotor task at the highest rotation speed and the minimum distance from the target as indices of accuracy and the standard deviations of time on target and distance from the target as indices of stability. Visuomotor accuracy was significantly enhanced in the HF group and disrupted in the LF group compared with the sham group, indicating frequency-dependent effects of rTMS. In contrast, both HF and LH rTMS demonstrated no significant change in visuomotor stability. Surprisingly, our findings demonstrated that the accuracy and stability of visuomotor performance may be differentially influenced by cerebellar rTMS suggesting that visuomotor accuracy and stability have different underlying neural mechanisms and revealed the possibility of training strategies based on cerebellar neuromodulation.